ENVIRONMENTAL RESEARCH OF THE FLUORINE CONCENTRATION IN DRINKING WATER IN POLTAVA REGION AND THE ANALYSIS OF THE HEALTH INFLUENCE - Toronchenko, O.M. (World of Medicine and Biology, 2013)
The territory of Poltava region belongs to Buchach fluorine hydrogeological provinces which groundwaters are characterized by a high content of fluorine. Drinking water with fluorine content higher than normal is the cause of endemic fluorosis among the population of the region, especially children. The highest incidence of fluorosis among the children is fixed in Pyriatyn, Lubny, Velyka Bagachka, Mashivka areas. To prevent the fluorine diseases of the population of the region it is necessary to implement the individual and collective preventive measures, search and develop new, safe technological methods of drinking water defluorination.
Keywords: fluorine; drinking water; fluorosis; incidence; prevention